2020
DOI: 10.1111/nyas.14553
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative and binocular disorders in preteens with computer vision syndrome: a cross‐sectional study

Abstract: To assess computer vision syndrome (CVS) in a preteen population through an adult-validated CVS questionnaire and to evaluate how digital devices affect accommodative and binocular vision, we enrolled 309 preteens in this cross-sectional study. An adult-validated CVS questionnaire adapted to preteens was used for all subjects. Visual acuity testing, unilateral and alternate cover tests, and tests for accommodative and vergence responses were performed for all preteens. The mean age was 10.75 ± 0.67 (10-12) yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
2
10
0
1
Order By: Relevance
“…Over the last few decades, the usage of handheld devices, including smartphones and tablets, has increased, especially during lockdowns due to the COVID-19 pandemic. Several ocular symptoms, including dry eye and binocular disabilities have also been reported after excessive usage of handheld devices [21,22]. When using a smartphone, the working distances are shorter than that found for typical near working distances [23], with these distances becoming even shorter when there is over 60 min of usage [24].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, the usage of handheld devices, including smartphones and tablets, has increased, especially during lockdowns due to the COVID-19 pandemic. Several ocular symptoms, including dry eye and binocular disabilities have also been reported after excessive usage of handheld devices [21,22]. When using a smartphone, the working distances are shorter than that found for typical near working distances [23], with these distances becoming even shorter when there is over 60 min of usage [24].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by De-Hita-Cantalejo et al showed that accommodative insufficiency is often associated with severe symptoms of CVS [ 9 ]. These results are similar with data from our study, showing that all patients with convergence insufficiency had eye fatigue and blurred vision when using gadgets.…”
Section: Discussionmentioning
confidence: 99%
“…The material used was a validated CVS screening questionnaire for children [14,15], ±2.00 D flippers, near-vision card, opaque occluder, translucent occluder, tape measure, prism bars, pointer (all previous material from Optometric Promotion, Madrid, Spain), Welch Allyn Streak Retinoscope (Welch Allyn, Leicestershire, UK), and Welch Allyn Autorefractometer (Welch Allyn, Leicestershire, UK). The measurements were made under the same light conditions and with the same material for all children.…”
Section: Materials and Measuresmentioning
confidence: 99%